Implementasi Pembelajaran Berdiferensiasi pada Pembelajaran IPAS Fase B Kelas IV Sekolah Dasar - Aditya Rini Kusumaningpuri (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
This research aims to describe (1) planning, (2) implementation, (3) evaluation, (4) (obstacles and (5) learning solutions for differentiating material on plant body parts in science learning stage B grade IV Elementary School. The research uses qualitative descriptive type with a case study approach. The sampling technique uses a purposive sampling technique. The data collection technique in this research is interviews, direct observation and document testing. Test the validity of the data by triangulating data sources and methods. The data analysis technique uses the Miles & flow analysis technique Huberman with an interactive model. The results of this research are that at the planning stage, teachers map student needs, create teaching modules along with Learning Objective Flow (ATP) and determine Criteria for Completion of Learning Objectives (KKTP). Teachers carry out learning with models that are differentiated based on content, process and product according to the results of the student's diagnosis, namely visual, auditory and kinesthetic. At the evaluation stage, this research used diagnostic, formative and summative assessments. It can be concluded that the implementation of differentiated learning is optimal and effective.